North Korea's Nuclear Development and Korean Peninsula Security Stability: A Defensive Realism Perspective (2017-2021) - Abdul Hakim, Annas; Zarkachi, Imam (Mediasi Journal of International Relations, 2023)
This research was motivated by North Korea's nuclear development with the aim of maintaining the stability of the country's security from external threats, but North Korea's nuclear development made countries in the Korean Peninsula region such as Japan and South Korea feel threatened, so the two countries also helped develop their military by making alliances to weaken North Korea. Therefore, researchers use the perspective of Defensive Realism to explain the impact of North Korea's nuclear development during Kim Jong Un's reign on the security stability of the Korean Peninsula in the period 2017 to 2021. The methods used are qualitative methods and literature analysis. The results showed that North Korea's nuclear development during the reign of Kim Jong Un had a significant impact on the security stability of the Korean Peninsula. This impact is in the form of increased security threats such as an arms race. Based on the analysis, it can be said that North Korea's nuclear development during the reign of Kim Jong Un has important implications for the security stability of the Korean Peninsula in the long run. Therefore, there needs to be a concerted effort to address this issue and ensure regional security stability.